Development of a simple algorithm for pre-fragment formation in proton-nucleus spallation reactions - Nicolis, Nikolaos George; Chatzikotelis, Athanasios (HNPS Advances in Nuclear Physics, 2023)
A Monte-Carlo algorithm is developed and coded in FORTRAN to calculate the energy, mass and charge distribution of the pre-fragments produced in proton induced spallation. The algorithm is based on Glauber’s theory together with a reasonable assumption on the type of the promptly emitted nucleons. For the evaporation stage, correlated values of pre-fragment mass, charge and excitation energy were fed into a properly modified version of the code MCEF (Monte-Carlo Evaporation-Fission) written in Java. A good agreement is obtained with the experimental mass and charge distributions of residues observed in 56Fe+p spallation reactions at 300, 500 and 750 MeV/A